Police : a field guide - Correia, David, 1968-; Wall, Tyler (London ; Brooklyn, NY : Verso, 2018)
"This guide will demystifiy the police language in order to better prepare everyone on the key issues of our time."
"Police: A Field Guide is an illustrated handbook to the methods, mythologies, and history that animate today's police. It is a survival manual for encounters with cops and police logic, whether it arrives in the shape of officer friendly, Tasers, curfews, non-compliance, or reformist discourses about so-called bad apples. In a series of short chapters, each focusing on a single term, such as the beat, order, badge, throw-down weapon, and much more, authors David Correia and Tyler Wall present a guide that reinvents and demystifies the language of policing in order to better prepare activists--and anyone with an open mind--on one of the key issues of our time: police brutality. In doing so, they begin to chart a future free of this violence--and of police." -- Publisher's description
Weaponology: Technologies and Tactics of Police Violence -- The Oath: Core Values of Police -- Models of Policing: How the Police are Organized and Defended -- Using the Force: How Police Impose Order -- Copspeak: How the Police See the World -- Epilogue: On a World Beyond Police.
Includes bibliographical references.
Keywords: Police; Police brutality; POLITICAL SCIENCE / Civil Rights; POLITICAL SCIENCE / Corruption & Misconduct; POLITICAL SCIENCE / Human Rights; Police; Police brutality